2021
DOI: 10.1186/s12877-021-02447-9
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent plasma treatment for patients of 80 years and older with COVID-19 pneumonia

Abstract: Background Older patients, frequently with multiple comorbidities, have a high mortality from COVID-19 infection. Convalescent plasma (CP) is a therapeutic option for these patients. Our objective is to retrospectively evaluate the efficacy and adverse events of CP treatment in this population group. Methods Forty one patients over 80 years old with COVID-19 pneumonia received CP added to standard treatment, 51.2% with high anti-SARS-CoV-2 IgG tite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Plasma with IgG titers of 1:3200 or higher reduced the risk of severe respiratory disease by 73%. 6) Similarly, Romon et al 10) reported in-hospital mortality rates of 26.8% for controls and 14.6% for patients administered CP (p = 0.131). Moreover, the ICU admission rates were 8.5% and 4.9%, respectively (p = 0.467).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Plasma with IgG titers of 1:3200 or higher reduced the risk of severe respiratory disease by 73%. 6) Similarly, Romon et al 10) reported in-hospital mortality rates of 26.8% for controls and 14.6% for patients administered CP (p = 0.131). Moreover, the ICU admission rates were 8.5% and 4.9%, respectively (p = 0.467).…”
Section: Discussionmentioning
confidence: 90%
“…1 ). 1 , 6 , 10 ) The characteristics of the included studies are presented in Table 1 . The critical appraisals for each study are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations